Edukasi pentingnya kesehatan reproduksi di kalangan mahasiswa STPKat St Fransiskus Asisi Semarang - Pradnya, Matilda Stella; Christyana, To Lidwina Prillya Indra; Setyaningsih, Mayang (INDRA: Jurnal Pengabdian kepada Masyarakat, 2024)
Reproductive health services and handling of its various aspects are important steps to ensure the health of families and public health. Among adolescents and productive age groups there is a high-risk sexual behavior and an increased incidence of co-occurring health conditions problem. Even though sex education has been provided in the school curriculum, it is still found that learning about reproductive health is only superficial and is stigmatized as taboo by society. College students, at a productive age, still need to learn about reproductive health. Promiscuous associations and stressors from college tasks can risk unwanted pregnancies, increased sexually transmitted diseases, and poor mental health. This community service activity aims to improve college students' knowledge and awareness of maintaining reproductive and mental health. This activity was given through teaching and discussions involving 76 college students. The expected outcome is to enhance students’ knowledge and implement it after graduation as a religion teacher. The result of this community service is increasing college student knowledge about reproductive health, especially related to the threats of free sex, early marriage, and mental reproductive health. Students seemed enthusiastic when paying attention to the course and actively participating in learning and discussion.